BRAND TRANSFER BY HANDPHONE CONSUMERS IN THE CITY OF JUANG BIREUEN - Ariska Ariska; Mulyadi Mulyadi; Imam Malik; Lakharis Inuzula (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
Various studies that have been carried out in the City of Juang Bireuen to see how far mobile phone consumers have switched to other brands, the findings or results of this study show a very significant impact on the switching of mobile phone brands, so that mobile phone manufacturers are charged with the desires that are of interest to consumers. The results carried out in the City of Juang Bireuen with respondents who had changed to another cellphone brand at least 1 time with 100 respondents the sample population showed that all averages were influenced by advertisements, price changes, and dissatisfaction in a cellphone brand, causing brand switching. The results of this study indicate that advertising has a positive and significant effect on the transfer of mobile phone brands. Likewise, price changes have a positive and significant effect on the transfer of mobile phone brands. Both with dissatisfaction have a positive effect on switching brands of mobile phones. Price changes strengthen the relationship between advertising and brand switching with interaction, meaning that price changes are purely an interaction variable. Likewise, price changes strengthen the relationship between dissatisfaction with brand switching and interaction. Based on the results of this study, there are several recommendations for consumers and mobile phone manufacturers, with increasing consumer interest in changing cellphone brands, it is an important task for manufacturers to be able to satisfy consumer desires